An optimized method to assess ototoxic effects in the lateral line of zebrafish (Danio rerio) embryos - Stengel, Daniel; Zindler, Florian; Braunbeck, Thomas (Comparative biochemistry and physiology. Part C, Toxicology & pharmacology, 2017)
In order to clarify the suitability of the lateral line of zebrafish (Danio rerio) embryos as a model for the screening of ototoxic (neurotoxic) effects, existing neuromast assays were adapted, improved and validated with a series of chemicals known or unknown for their ototoxic potential (caffeine copper sulfate, dichlorvos, 2.4-dinitrotoluene, neomycin, 4-nonylphenol, perfluorooctanesulfonic acid). Present methods were improved by (1) the introduction of a 4-step scoring system, (2) the selection of neuromasts from both the anterior and posterior lateral line systems, (3) a combined DASPEI/DAPI staining applied after both a continuous and pulse exposure scenario, and (4) an additional screening for nuclear fragmentation. Acute toxicities of the model substances were determined by means of the fish embryo test as specified in OECD TG 236, and EC10 concentrations were used as the highest test concentration in the neuromast assay. The enhanced neuromast assay identified known ototoxic substances such as neomycin and copper sulfate as ototoxic at sensitivities similar to those of established methods, with pulse exposure leading to stronger effects than continuous exposure. Except for caffeine, all substances tested (dichlorvos, 2.4-dinitrotoluene, 4-nonylphenol, perfluorooctanesulfonic acid) produced significant toxic effects in neuromasts at EC10 concentrations. Depending on the test substances and their location along the lateral line, specific neuromasts differed in sensitivity. Generally, neuromasts proved more sensitive in the pulse exposure scenario. Whereas for neomycin and copper sulfate neuromasts located along the anterior lateral line were more sensitive, posterior lateral line neuromasts proved more sensitive for the other test substances. Nuclear fragmentation could not only be associated with all test substances, but, albeit at lower frequencies, also with negative controls, and could, therefore, not be assigned specifically to chemical damage. The study thus documented that for a comprehensive evaluation of lateral line damage both neuromasts from the anterior and the posterior lateral line have to be considered. Given the apparently rapid regeneration of hair cells, pulse exposure seems more appropriate for the identification of lateral line neurotoxicity than continuous exposure.